Menganalisis Sekolah Dasar Sebagai Organisasi Pendidikan Sistem Sosial - Idawati Idawati; Nurul Muhklisah; Hardianto Hardianto; Nurul Hidayah; Armawanti Yuanata; Suratmi Dahlan (Journal on Education, 2025)
Schools as institutions must be open and adaptable to external changes in order to remain effective and sustainable especially in today's modern society where schools must function as both social and cultural systems. Through proper education, both individual and social aspects can develop in harmony, aligning with Indonesia’s motto —Unity in Diversity. Modern society is characterized by rational thinking, future-oriented perspectives, time consciousness, openness, and objective reasoning. Based on this background, this paper aims to examine schools as a system of social interaction. This study employs a qualitative approach, with data collected from relevant literature, including books, journals, and interviews. School is a concept with a dual meaning. First, it refers to a building or physical environment with all its facilities, serving as a place where a specific group of people undergoes a particular educational process. Thus, when we hear the word "school," what comes to mind is such a physical environment. This perception of school as a physical setting is reinforced by the relative uniformity in the design of buildings and facilities, making it possible to say that the physical conditions of schools of the same type and level are relatively similar.As a social system, a school is an accumulation of integral social components that interact and depend on one another. The microcosmic approach views a school as a world of its own, containing essential elements that define a society, such as leadership, governance, community members, rules, norms, and social groups.